Carbohydrases and phytase with rice bran, effects on amino acid digestibility and energy use in broiler chickens. (30th September 2019) - Gallardo, C.; Dadalt, J. C.; Trindade Neto, M. A.
Abstract : Protein sources from cereals are used in broiler diets, usually in order to reduce feeding costs. However, their efficient use in poultry diets is limited by the level of fiber whose compounds are resistant to digestion in the small intestine; due to this sugars are not digested by endogenous poultry enzymes. The aim of this study was to determine the effect of multi-carbohydrase (MC ) and phytase (Phy ) on the total retention of nutrients, retention of apparent metabolizable energy corrected for nitrogen (AME N ) (trial 1) and apparent and standardized ileal digestibility of amino acids (trial 2) of rice bran (RB ). A total of 245-day-old male broilers (Cobb 500) was distributed at 21-day-old in a completely randomized design in a 2 × 2 + 1 (0 and 200 mg/kg MC; 0 and 50 mg/kg Phy, and basal diet – BD ) factorial arrangement of treatments, to give seven replicates and seven birds per replicate. The BD based on corn (trial 1) and cornstarch and casein (trial 2) was used only to determine the coefficients of retention of nutrients and energy, and coefficients of digestibility of amino acids of the RB. The test diets were made by mixing BD and RB 7 : 3 wt/wt basis. There was interaction ( P <0.05) between MC × Phy for DM, nitrogen and AMEN, retention and no interaction ( P >0.05) for ash, calcium, phosphorous and NDF was observed. Enzymes interacted ( P <0.05) on standardized ileal digestibility of arginine, histidine, leucine, methionine, phenylalanine, threonine, valine, aspartic acid, glutamic acid, proline and serine. Dietary combination of MC and Phy resulted in higher ( P <0.05) standardized digestibility of arginine, histidine, methionine and threonine relative to single enzyme supplementation or control diet without enzymes. Enzyme isolated inclusions in the diets improved ( P <0.05) standardized digestibility of methionine. The supplementation of carbohydrases and Phy in RB will improve the nitrogen, energy and amino acids utilization for broiler chickens.